Optimal fear of floating: the role of currency mismatches and fiscal constraints - Eduardo J.J. Ganapolsky (Federal Reserve Bank of Atlanta, 2003)
Evidence suggests that developing countries are much more concerned with stabilizing the nominal exchange rate than developed countries. This paper presents a model to explain this observation, based on the hypotheses that both interventions and depreciations are costly. Interventions are costly because they generate a financial need in a fiscally constrained government that relies solely on distortionary taxes. Depreciations are costly because the country, in particular its financial sector, is exposed to a currency mismatch between its assets and its liabilities that is not effectively hedged. The results suggest that the amount of intervention will depend on the degree of currency mismatch between assets and liabilities, the elasticity of money demand, and the relative size of the financial system. It would be expected that countries with a high degree of currency mismatch and large financial sectors would intervene heavily in foreign exchange markets, as long as the money demand is not too sensitive to the nominal interest rate.
Keywords: 330